Aquathermolysis of heavy oil catalyzed by transition metal salts and clay - Du, Yingna; Zhang, Liyuan; Jing, Rui; Li, Yongfei; Yang, Bo; Chen, Gang (Comptes Rendus. Chimie, 2023)
Currently, researchers have indicated that inorganic minerals in reservoirs, such as clay minerals, carbonates and quartz, can catalyze the evolution of organic matter into oil and gas. Therefore it is reasonable to believe that the minerals in reservoirs may act as a catalyst support with the metal-containing catalyst added from outside during the thermal recovery of heavy oil. This paper studied the aquathermolysis of heavy oil catalyzed by minerals and transition metal. The reaction conditions of two heavy oil samples were investigated. The results show that the optimal reaction conditions of heavy oil from Xinjiang Baikouquan Oilfield (XBO) are the reaction temperature of 250 °C and the reaction time of 6 h; for the crude oil from Xinjiang Tahe Oilfield (XTO), the optimal reaction conditions are determined to be the reaction temperature of 250 °C and the reaction time of 12 h, the water–oil ratio of the two oils is 0.3. Under optimal conditions, viscosity and pour point of heavy oil are significantly reduced. Differential scanning calorimetry (DSC), GC-MS analysis, thermogravimetric analysis (TGA), and elemental analysis were used to study the properties of the two heavy oil samples before and after reaction to explore the mechanism of the catalyzed aquathermolysis of heavy oil. This work will benefit the related heavy oil recovery work in this field.